PENGEMBANGAN MEDIA CERGAM SUBTEMA PERKEMBANGAN TEKNOLOGI PRODUKSI PANGAN UNTUK MENINGKATKAN MINAT BACA KELAS III SEKOLAH DASAR - Nur Afwa Mumtazah; Galuh Kartika Dewi; Satrio Wibowo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research was motivated by developing picture story learning media to increase reading interest for class III students at SDN Pilang 1, in learning the Sub-theme of Development of Food Production Technology. The problem students found when researchers conducted observations was that most of the collection of reading books as a learning resource still only contained reading texts, with a lack of pictures containing the content of the reading. This causes students' interest in reading to decrease because books do not contain pictures and material that supports the reading content. Each individual student's interest in reading is different, researchers found that students will read books if they have an interest in reading. The aim of this research is to make class III students at SDN Pilang 1 interested in reading. Research and Development (R&D) is the method that will be used in this research. In this research, the subjects used were class III elementary school students, totaling 18 students. Data were collected using student reading interest observation sheets. And material expert validation sheets and media expert validation results. From the material expert validation results assessed by the validator lecturer, it is known that the average validation result is 4.4 with a percentage of 82.6%, while the media expert validation results assessed by the validator lecturer, it is known that the average validation result is 4.1 with a percentage of 82%. % included in the eligible category. And the results of observations on students' reading interest, the researcher distributed questionnaires to class III students, the results of the questionnaire after using picture story media were with a reading interest mean percentage of 80,5% with good criteria.